Assembling a Low‐volume Biofuel Cell on a Screen‐printed Electrode for Glucose Sensing. Issue 10 (13th April 2022) - Becker, Jana M.; Lielpetere, Anna; Szczesny, Julian; Ruff, Adrian; Conzuelo, Felipe; Schuhmann, Wolfgang
Abstract: An enzymatic biofuel cell is integrated on a screen‐printed electrode as a basis for a self‐powered biosensor. A glucose/O2 biofuel cell consisting of a pyrroloquinoline quinone‐dependent glucose dehydrogenase embedded within an Os‐complex modified redox polymer bioanode to oxidize glucose and a non‐limiting bilirubin oxidase‐based gas diffusion biocathode in the direct‐electron transfer regime for the reduction of O2 showed a glucose‐dependent current and power output. For full integration on a single screen‐printed electrode, a miniaturized agar salt bridge was introduced between the two bioelectrodes to ensure operation of the assembly in a two‐compartment configuration with each electrode operating at optimal conditions. Abstract :